A simple model for submaximal exchange through the Strait of Gibraltar - Delgado, Javier; García Lafuente, Jesús; Vargas, Juan Miguel (Scientia Marina, 2001)
This work presents a simple two-layer model for the water exchange through the Strait of Gibraltar. The model is inspired by the work of Bormans and Garrett (1989) and focus on the case of submaximal exchange with an unique hydraulic control at the section of minimum cross-area. The first part describes the model and justifies the assumed simplifications. Some aspects regarding its performance are also analysed. The second part applies the model to interpret the seasonal signals in the exchanged flows that were observed during the Canary Islands Azores Gibraltar Observations (CANIGO) project. These signals are compatible with submaximal exchange, which suggests that the oceanographic conditions in the nearby Alboran Sea are able to influence the exchange via interface depth variations.